2021
DOI: 10.4143/crt.2020.803
|View full text |Cite
|
Sign up to set email alerts
|

A National Study of Life-Sustaining Treatments in South Korea: What Factors Affect Decision-Making?

Abstract: This cross-sectional study investigated the status of life-sustaining treatment (LST) practices and identified characteristics and factors influencing decision-making practices. Materials and Methods The National Agency for Management of Life-sustaining Treatment retains records provided by doctors regarding patients subject to LST implementation. A total of 71,327 patients receiving LST were identified. We analyzed all nationally reported data between February 2018 and October 2019. Indicators such as the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…In the current study, we found that the self-determination rate of LST was 31% and the mean time interval from self-determination to implementation of LST was approximately 8.6 days, which is higher and longer than those from previous studies [1,2,5]. Indeed, the selfdetermination rates from recent single center and national retrospective studies were 29% and 33.5%, respectively [6,7]. There was little difference in the self-determination rate as a result of differences in the hospital settings, enrolled subjects, or research period.…”
Section: Discussionmentioning
confidence: 41%
“…In the current study, we found that the self-determination rate of LST was 31% and the mean time interval from self-determination to implementation of LST was approximately 8.6 days, which is higher and longer than those from previous studies [1,2,5]. Indeed, the selfdetermination rates from recent single center and national retrospective studies were 29% and 33.5%, respectively [6,7]. There was little difference in the self-determination rate as a result of differences in the hospital settings, enrolled subjects, or research period.…”
Section: Discussionmentioning
confidence: 41%
“…Recently reported limitations of clinician-family end-of-life conferences include insufficient information exchange about the patient’s values and preferences and deficient deliberation; this implies that the communication skills of clinicians need to be improved [ 18 , 59 ]. Regarding guidelines per se, these may not effectively address problems of reaching consensus decisions, prognostication challenges, barriers in communication, patient palliative care needs, and physician-related variability in end-of-life decision-making [ 58 62 ]. Absence of association or negative associations between a number of the end-of-life practice variables and treatment limitation were noted, and appear to be counter-intuitive and difficult to explain.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, around one-third of the patients in Korea made decisions for LST on their own and had a short median time of two days from confirmation of the EOL process to death [ 9 , 10 ]. These results appear to reflect the increased awareness of Korean patient autonomy by taking charge of their own decisions compared to previous findings, which showed that all do-not-resuscitate consents were made between the physician and family without involving the patient before the enforcement of this law [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%